2024
DOI: 10.14740/gr1707
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Overview of Sarcopenia, Frailty, and Malnutrition in Patients With Liver Cirrhosis

Alexander Kusnik,
Amulya Penmetsa,
Farooq Chaudhary
et al.

Abstract: Sarcopenia, frailty, and malnutrition in patients with liver cirrhosis are commonly observed and are associated with higher long-term mortality. Therefore, recognizing patients with increased nutritional risk and providing recommended interventions are essential in the long- and short-term management of cirrhosis, especially as alcoholic and non-alcoholic fatty liver disease continues to rise. Various assessment tools are available to gauge frailty and malnutrition but are infrequently used. Given the global b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Additional protection arises from the liver-specific gene CYP39A1, which demonstrates hepatoprotective properties and is more prevalent in females [ 27 ]. Overall, the factors contributing to the difference in HCC development between sexes are not fully understood and are likely a result of a complex interplay involving epigenetic influences, lifestyle, diet, behavioral factors, and hormonal differences [ 2 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional protection arises from the liver-specific gene CYP39A1, which demonstrates hepatoprotective properties and is more prevalent in females [ 27 ]. Overall, the factors contributing to the difference in HCC development between sexes are not fully understood and are likely a result of a complex interplay involving epigenetic influences, lifestyle, diet, behavioral factors, and hormonal differences [ 2 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with cirrhosis, malnutrition is characterized by depletion of skeletal muscle and adipose tissue mass, with the main nutritional consequences of the loss of skeletal muscle mass ( 79 ). Sarcopenia can be measured by handgrip strength (HGS) in addition to the Skeletal Muscle Index (SMI) ( 41 ).…”
Section: Sarcopeniamentioning
confidence: 99%
“…Although it is costly to perform CT specifically to calculate SMI, patients are exposed to unnecessary radiation. Notably, patients with cirrhosis often undergo CT for other reasons (e.g., to screen for hepatocellular carcinoma), so this approach is clinically feasible; and SMI values calculated from thoracic spine 12 (T12) levels also showed a correlation with mortality ( 41 , 79 ). Therefore, CT images at the T12 level can be used to calculate SMI for those patients who do not have abdominal CT. A review indicated that ultrasound testing for sarcopenia in patients with advanced liver disease is safe, feasible, and shows good correlation with gold standard measurements of sarcopenia and can be used as a valid tool in daily practice ( 85 ).…”
Section: Sarcopeniamentioning
confidence: 99%